The effects of glazing with plasma-activated water generated by a piezoelectric direct discharge plasma system on whiteleg shrimp (Litopenaeus vannamei). (15th January 2022) - Herianto, Samuel; Shih, Ming-Kuei; Lin, Chia-Min; Hung, Yu-Chi; Hsieh, Chang-Wei; Wu, Jong-Shinn; Chen, Min-Hung; Chen, Hsiu-Ling; Hou, Chih-Yao
Abstract: Multiple hard-to-reach spots on foods with rough surfaces (such as shrimp) limit the maximal exposure to antibacterial agents. In this study, we successfully generated plasma-activated water (PAW) using a low energy-consuming source of a non-thermal atmospheric piezoelectric direct discharge plasma (PDDP) system and evaluated its effectiveness as a glazing agent on shrimp, facilitating a whole surface treatment. During generation, a feeding gas mixture of N2 (80%): O2 (20%) and N2 (85%): O2 (15%) was revealed to optimally produce reactive oxygen species (ROS) such as H2 O2 (60.7 ± 0.2 mg/L) and O3 (0.45 ± 0.02 mg/L) as well as reactive nitrogen species (RNS) such as NO2 ‾ (48.5 ± 0.5 mg/L). Furthermore, the application of PAW-glazing on shrimps was demonstrated to be capable of maintaining microbial growth below 6 log CFU/g throughout the storage period (9 days). This approach also possessed the capacity to retard the loss of both physical (color and firmness) and chemical characteristics (pH, total volatile basic nitrogen [TVBN], and thiobarbituric acid reactive substance [TBARS]) of PAW-glazed shrimps. Finally, this study demonstrated the effectiveness of glazing with PAW generated from the PDDP system as a potential prevention agent for shrimps. Graphical abstract: Image 1 Highlights: PAW was generated using a low energy-consuming source of non-thermal PDDP system. The optimally generated PAW contains ROS (H2 O2 and O3 ) and RNS (NO2 ‾). Developing a potential shrimp preservation method by glazing with PDDP-based PAW. This approach offers capacity for inhibition of microbial growth. Both physical and chemical characteristics of glazed shrimps are not compromised.